2016
DOI: 10.1093/annonc/mdw272
|View full text |Cite
|
Sign up to set email alerts
|

Best practice guidelines in the psychosocial management of HPV-related head and neck cancer: recommendations from the European Head and Neck Cancer Society's Make Sense Campaign

Abstract: Over the past three decades, oral human papillomavirus (HPV) has been associated with an increase in the incidence of oropharyngeal squamous cell carcinoma (OPSCC) in several countries. Specialist oncologists in head and neck cancer are observing a wider range of demographics, sexual behaviours, and survival outcomes with their patients. Additionally, there are fewer smokers, consumers of alcohol, or people of lower socioeconomic status than in previous decades. In order to support patients, the European Head … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 55 publications
0
25
0
2
Order By: Relevance
“…The cervical cancer literature has demonstrated that a HPV diagnosis has the potential to cause feelings of stigma and shame in addition to the anxiety and health concerns usually associated with abnormal cervical screening results (McCaffery, Waller, Nazroo, & Wardle, ). Sexual relationships may be affected due to concern over the sexual transmission of HPV (Taberna, Inglehart, Pickard, Fakhry, & Agrawal, ) and clinicians should be prepared to potentially talk about these concerns (Reich et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The cervical cancer literature has demonstrated that a HPV diagnosis has the potential to cause feelings of stigma and shame in addition to the anxiety and health concerns usually associated with abnormal cervical screening results (McCaffery, Waller, Nazroo, & Wardle, ). Sexual relationships may be affected due to concern over the sexual transmission of HPV (Taberna, Inglehart, Pickard, Fakhry, & Agrawal, ) and clinicians should be prepared to potentially talk about these concerns (Reich et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Fear of recurrence is prevalent in HNC [61] and it concerns clinicians [7] and can influence follow-up preferences [16]. However, despite regular follow-up being reassuring [4], it inadequately addresses patients' holistic psychosocial needs [5e7], including in HPV-related HNC despite lower risks [62]. PIFU may better address these needs [19] and [patient education sessions] to reflect and debrief and move forward with their lives after their treatment, and that's been a full day of hospital site where there's been a lot of supportive interaction.…”
Section: Discussionmentioning
confidence: 99%
“…When a clinician delivers a cancer diagnosis, it creates distress and anxiety for the patient, which may then be amplified by guilt and self-blame when the malignancy is linked to a sexually transmitted disease [ 25 ]. Reich et al emphasized the importance of minimizing self-blame by ensuring the patient understands that HPV-16 can be shared amongst long-term partners, without the occurrence of infidelity, despite its link to increased lifetime of sexual partners and unprotected sexual intercourse [ 26 ]. It is common for patients to have concerns regarding the likelihood of their partner developing an HPV-related cancer.…”
Section: Discussionmentioning
confidence: 99%